THE IMPLICATURE IN FLOUTING MAXIM OF RELATION BY THE MAIN CHARACTER IN IRON MAN 2 MOVIE - PRAMESWARI, LATSA NADA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language takes an important role in human life. It is a tool for communication. People can get what they want and express their feelings by doing communication. In order to have good communication, the speaker and theThis study uses qualitative approach because the writer analyzes conversations in movie. The result of the study shows that there are 7 reasons why the main character flouts the maxim. This study also shows that there are 20 utterances containing flouting maxim of relation. Furthermore, this study alsoreveals that the using of flouting maxim of relation makes conversation moreinteresting.Hopefully, this study will inspire the next researchers to broaden their pointof view in order to look for the problems of the study. Furthermore, the writer alsosuggests the next researchers to look for other subject to be analyzed and use othertheories to analyze the data. Keywords: Cooperative principle, flouting maxim of relation, implicature, iron man 2 movie.hearer have to obey "Cooperative Principle". However, there is a phenomenon when occasionally someone says one thing but he/ she means another. It usually happens with flouting maxim. One kind of flouting maxim is flouting maxim of relation. It occurs when a speaker or hearer responses which is very obviously irrelevant to the topic. The phenomenon is presented in the Iron Man 2 movie. This study aims to reveal the reasons why the main character flouts maxim of relation and what the impact to the conversation is.